Advanced Satellite-Based Spectral Techniques for Identifying and Quantifying Soil Clay Minerals - Devnita, Rina; Arifin, Mahfud; Ramadhan, Ilmi (Indonesian Journal on Geoscience, 2025)
Soil mineral plays an important role in agriculture due to its ability in influencing soil physical and chemical characteristics, and therefore is important to be identified. The techniques for identifying soil minerals, such as the utilization of a polarization microscope and X-Ray Diffraction (XRD), are often laborious, time-consuming, and costly. This study aims to identify and to quantify soil clay minerals by using Hyperion EO-1 imagery and XRD methods, and to reveal the effectiveness of using satellite imagery to determine soil minerals. Spectral signatures from Hyperion EO-1 were extracted in alignment with the soil sampling coordinate locations, and spectral data processing methods such as Continuum Removal (CR), and Savitzky-Golay filtering were used to identify and to quantify minerals. The results show that hyperspectral analysis revealed distinct spectral absorption features, and it could identify kaolinite, chlorite, goethite, hematite, and plagioclase. Meanwhile, XRD analysis confirmed kaolinite and chlorite, consistent with the hyperspectral observations. A key advantage of the spectral absorption technique for raw soil was its ability to identify not only clay minerals, but also both primary and secondary minerals, such as plagioclase, hematite, and goethite, that remain unidentified when using the XRD method with iron removal pre-treatment. Although hyperspectral imagery was successful in identifying soil minerals, there are still some limitations that require further refinement, especially while conducting quantification. The findings underscored the potential of satellite-based hyperspectral analysis as a rapid alternative approach to soil mineral identification that can reduce reliance on laboratory-based methods.